EVALUATING TURKEY HUNTER ATTITUDES ON WILDLIFE MANAGEMENT AREAS IN MISSISSIPPI - Douglas A. Little; Jacob L. Bowman; George A. Hurst; Ronald S. Seiss; Donna L. Minnis (Wildlife Society Bulletin)
Abstract: Hunter attitudes should be considered when developing regulations regarding hunting, especially on public wildlife management areas (WMAs). Therefore, we conducted a mail survey of spring gobbler hunters following the 1998 spring turkey (Meleagris gallopavo) season to assess quality of hunting on 29 WMAs and hunter attitudes toward current and potential regulations. We distributed surveys to individuals (n = 3,764) who hunted on a WMA in 1998 and obtained a response from 63.2% (n = 2,379) after 2 mailings. Most (50%) respondents had a good‐excellent experience, but 19% reported having a poor–very poor experience. Hunt quality increased as number of days disturbed by other hunters decreased, number of weekdays and weekend days hunted increased, and as the number of days a respondent heard, saw, worked, and harvested a male increased. We developed a logistic regression model to predict hunt quality (good vs. poor) using the stepwise variable selection procedure (α = 0.05) to determine significant variables. Number of days respondents hunted, number of days they heard, saw, and worked a male, and number of days disturbed by other hunters were significant predictors of hunt quality. The number of days a male was harvested was not a significant predictor variable. The hunt quality model correctly identified >75% of respondents. Respondent attitudes towards 8 current and potential regulations were evaluated. Respondents supported controlling the number of hunters during periods of high hunting pressure (57%), closing some roads to restrict access by motorized vehicles (79%), protecting juvenile males (jakes) from harvest (87%), and the method of protecting jakes under the current regulations which allow the harvest of adult males or males with a ≥6‐in beard (91%).